Small crumbled diet versus powdered diet in restricted feeding management of juvenile Nile tilapia - doi: 10.4025/actascianimsci.v35i2.16767 - Francisco Roberto dos Santos Lima; Michael Masaki Freitas Akao; José Nacélio Oliveira-Segundo; Marcelo Vinícius do Carmo e Sá (Acta Scientiarum. Animal Sciences, 2012)
The pellet size of the diet can affect both fish growth performance and the water quality of therearing units. The present work assessed the effects of feeding juvenile Nile tilapia, Oreochromis niloticus (L.) asmall crumbled diet (SCD; 0.8 mm) on water quality and growth performance. Fish were reared for six weeks intwenty 250-L polyethylene outdoor tanks at a density of 10 juveniles tank-1 (40 fish m-3). There were two feedingrates (standard and restricted) and two types of artificial fish diet (powdered and SCD). The standard feedingrates were reduced by 30% for restricted feeding. The concentrations of free CO2, reactive phosphorus, totalammonia nitrogen (TAN) and nitrite were higher in the full-fed tanks relative to the restricted-fed tanks. In thestandard feeding rate groups, those tanks fed SCD had lower TAN and nitrite concentrations than tanks fed apowdered diet. The final body weight and specific growth rate of fish fed a restricted SCD were higher than thefull-fed tanks. The higher levels of food waste in the powdered-diet tanks lead to impairment of fish growthperformance.